Prognostic prediction of lung adenocarcinoma by integrative analysis of RHOH expression and methylation. (29th January 2023) - Kuang, Muyu; Zhou, Zhenhua; Lu, Zhongyuan; Shen, Weina; Ge, Haiyan; Tao, Xiaoting; Zhao, Yue; Zhuge, Lingdun; Sun, Yihua; Ji, Dongmei; Zhang, Huibiao
Abstract: Background and objective: The development of epigenetics holds great promise for diagnosis and treatment of lung adenocarcinoma (LUAD). The purpose of this work was to analyze the correlation between Ras Homolog Gene Family Member H (RHOH) expression and methylation in patients with LUAD and its association with survival. Methods: Data related to gene expression, DNA methylation, and clinical features of LUAD from The Cancer Genome Atlas (TCGA) database were analyzed. A total of 50 patients were included in verification group. The methylation level of RHOH in verification group was detected by bisulfite amplicon sequencing. Results: The RHOH methylation level in TCGA cohort was significantly and negatively correlated with its expression level (Cor = −0.5, p = 2.687e−33). Patients with hypermethylation and low expression of RHOH had significantly worse prognosis than patients with hypomethylation and low expression of RHOH (TCGA: p = 0.004; validation cohort: p = 0.006, HR: 4.740, 95% CI: 1.567–14.340). Conclusion: Our research revealed that RHOH may prove to be a new potential prognostic predictor for LUAD patients. Abstract : RHOH methylation and gene expression were both related to the prognosis of LUAD patients, and the combined analysis of RHOH methylation and expression could better predict the prognosis of LUAD patients.